Determination of 3D Gravity Source and Its Depth Beneath Cameroon Volcanic Line (CVL) Using DEXP Transformation - Ekolle Ndinde Eya; Vasilevskiy Alexandr; Esin Egor (Russian Journal of Earth Sciences)
The Cameroon Volcanic Line (CVL), which is around 1600 km long, the Adamawa Plateau, the northern sedimentary basins, the Central African Shear Zone, and the northern boundary between the Pan-African Mobile Belt and Congo Craton are the primary geological features of Cameroon. A good number of authors have attempted to comprehend the geology and gravity field along the CVL by using gravitational data from the EGM2008 model to analyze the gravity effects in areas around Cameroon and the CVL with a focus on its structures and subsurface characteristics. Despite the fact that many authors have written on the subject matter, more emphasis has to be placed on the determination of the gravity source and depth beneath the CVL. Experimental gravity field model XGM2019e_2159 and DTU21 data were used in this research to estimate the depth of the gravity source. Both DEXP (Depth from Extreme Points) and spectral analysis were carried out to complement the results and accuracy of the techniques. The main focus of this research is to investigate the gravity source depth of CVL using DEXP as the main approach to illustrate its application in solving geophysical and geologic problems and reveal details of volcanic structures beneath the CVL. In this work, we describe the steps taken to calculate the anomalous gravity field and regional and residual gravitational effects. We further performed application of the DEXP transformation of 3D gravity field distribution to produce a 3D model for the depth of gravity sources.